자연재해가 지역경제에 미치는 영향 - 박한나(Park, Han-na); 송재민(Song, Jaemin) (국토계획, 2016)
자연재해가 증가함에 따라 최근 자연재해가 경제 성장에 미치는 영향에 대한 관심이 증가하고 있다. 하지만 자연재해가 경제성장에 미치는영향은 연구에 따라 그 결과가 상이해왔다. 국외몇몇 연구의 경우 자연재해 발생 직후 일정기간동안 국내총생산이 대체적으로 증가함을 보여 긍정적인 영향(Albala- Bertrand, 1993; Dacy and Kunreuther, 1969)을 미친 것으로 나타난 반면, 류문현 외(2012)의 연구에서는 자연재해가 국내총생산을 감소시키는 것으로 나타났다. 한편, IDB 연구보고서(2010)에 따르면 자연재해가 경제성장에 유의한 영향을 미치지 않는 것으로 나타났다. 이와같은 연구 결과의 차이는 분석모형이나 자연재해의대상, 분석지역, 분석 시점, 분석 이용 경제성장의지표 등의 차이로 인한 것으로 이해될 수 있다. 국내의 경우 최근 자연재해로 인한 피해가 급증하고 있으며, 이로 인한 경제에 미치는 직‧간접적영향이 증대되고 있음에도 불구하고 이와 관련된실증적 연구가 많지 않다. 앞서 언급된 바와 같이자연재해가 경제에 미치는 영향은 재해의 특성 및발생 지역의 물리, 사회 및 경제적 특성에 따라 상이함으로 국내 지역을 대상으로 한 실증 연구가 필수적이다. 또한 이와 같은 연구 결과는 방재와 경제 정책과의 연계 및 활용을 가능하게 할 것으로기대되는 바이다. 이와 같은 배경에서 본 연구의 목적은 우리나라를 대상으로 자연재해가 지역경제에 미치는 효과를밝히는 것이다. 이를 위하여 자연재해가 경제에 미치는 장단기 영향, 계절별 재해 특성 영향 및 산업별 영향을 강원도, 경상북도, 충청남도, 충청북도의69개 시군을 대상으로 분석하였다1). 본 연구의 결과는 자연재해 관리가 지역안전 차원뿐만 아니라향후 지역경제발전을 위한 정책 마련에 구체적인근거로 활용될 수 있을 것으로 기대되는 바이다. With the increasing frequency as well as the strength of natural disaster, there has been an attempt to empirically assess the impacts of natural disaster on the local economy in other countries; however, there is a serious lack of research on the case of Korea. Against this backdrop, the research aims to investigate the impact of natural disaster on the local economy for 69 municipalities, by conducting a panel analysis. Data on property loss caused by natural disaster and its lagged values have been included as independent variables with other control variables including population, financial dependence ratio and tax revenue, while gross regional product value has been used as a dependent variable in the model. The results demonstrate that disaster damages generally have a negative impact with time-lag effects on the economy. In particular, the damage during the summer is a critical barrier to the economic growth. But, for the case of secondary industry, a stimulus effect of disaster damage exists, bringing about a positive impact on the economic growth in the sector. The findings from the study support a rational for the further strengthened efforts for disaster risk reduction and mitigation not only for developing as a natural disaster resilient city but also for creating a resilient economy in the country. KCI Citation Count: 8